Urgensi Pembentukan Undang-Undang Kemitraan Untuk Pengemudi Ojek Online - Aryaputri, Aqila Shafiqa; Mufti, Muhammad Wildan; Siregar, Tiara Rebecca Kezia; Maulana, Muhammad Irfan (Jurnal Hukum Statuta, 2023)
Technological advancements have transformed the transportation sector with the emergence of online motorcycle taxi services, such as PT Gojek, significantly impacting Indonesia's digital economy. However, the legal status of online motorcycle taxi drivers, deemed "partners," has sparked considerable debate regarding their rights and obligations. This study employs a normative juridical method to analyze relevant legislation and legal doctrines. The findings indicate that the current partnership arrangements fail to meet the principles of equitable and fair partnerships. Drivers often find themselves in disadvantaged positions, lacking social security and workers' rights. Consequently, the partnership relationship requires clearer regulations to protect drivers' rights. It is recommended that partnership agreements be revised to reflect the principles of mutualism and equality, and that the government should play a more active role in monitoring the implementation of regulations to ensure the welfare of online motorcycle taxi drivers.